College students’ academic stress during the Covid-19 pandemic: The influence of hardiness, coping strategy, social support, and demographic factorsand - Neneng Tati Sumiati; Maftukhatus Sakiinah; Rena Latifa (Jurnal Cakrawala Promkes, 2023)
Several research results show that during the COVID-19 pandemic, academic stress experienced by college students increased. They experience changes in how they learn, have difficulty staying focused, and are unproductive during the covid-19 pandemic. This study tests factors influencing college students’ academic stress during the covid-19 pandemic. We hypothesized that hardiness, coping strategy, social support, and demographic factors influence academic stress. The sampling technique employed a non-probability sampling technique with a purposive sampling type, with the criteria for college students in Jabodetabek who did distance learning during Covid-19 Pandemic. Three hundred-six participants met the research criteria. Data were collected by academic stress and hardiness scales and; adapting the interpersonal support evaluation list and coping styles scale. Validation of the research instrument using confirmatory factor analysis (CFA) through Lisrel 8.8 software. Hypothesis testing using multiple regression with SPSS software version 20.0. Hardiness, coping strategy (problem-focused-coping and emotional-focused-coping), social support (tangible, appraisal, self-esteem, and belonging)- and demographic factors (gender, level of study) have a significant effect on college student’s academic stress during the covid-19 pandemic (r2=28.2%, p<.001). Variables that have a significant effect on academic stress are emotional-focused-coping (B=0.361, p<.001), self-esteem-support (B=0.117, p<.050), belonging-support (B=-0.271, p<.001) and gender (B=6.885, p<.001). Academic stress is influenced by hardiness, coping strategies, social support, and demographic factors. College students’ academic stress will decrease if students get social support in the form of self-esteem-support and belonging support. The use of highly emotional-focused coping strategies will increase academic stress.